2019
DOI: 10.1021/acs.jpcb.9b00271
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Occupancy and Vibrational Dynamics of Spatially Patterned Water Molecules

Abstract: We performed first-principles molecular dynamics simulations of relatively dilute aqueous solutions of sulfate and thiosulfate dianions to analyze the structure, dynamics, and vibrational spectral properties of water molecules around the solute, especially the spatially patterned solvent molecules in the first solvation layer and the extended layers. This study also involves the investigation of dynamics of dangling OH groups in these layers and their role in patterning the water molecules around the dianions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…13,14 An important contribution to this field was the development of ab initio MD (AIMD), where forces are derived from the electronic structure, 15,16 usually in the framework of density functional theory (DFT), 17 which provides the capability of studying non-additivity effects in the dynamics of ions solvation shells. AIMD simulations, using the Car-Parrinello and Born-Oppenheimer schemes, of cations [18][19][20][21][22][23] and anions, 24,25 have been mostly conducted on an isolated ion in pure liquid water, with no counterions in solution. Electrolyte solutions, on the other hand, have been subject to only a few AIMD studies, including the characterization of the dissociation of the NaCl in water, 26 the cooperative ionic effects are of the Na + and Cl À on the hydrogen bonding network, 27 and the influence of a static electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 An important contribution to this field was the development of ab initio MD (AIMD), where forces are derived from the electronic structure, 15,16 usually in the framework of density functional theory (DFT), 17 which provides the capability of studying non-additivity effects in the dynamics of ions solvation shells. AIMD simulations, using the Car-Parrinello and Born-Oppenheimer schemes, of cations [18][19][20][21][22][23] and anions, 24,25 have been mostly conducted on an isolated ion in pure liquid water, with no counterions in solution. Electrolyte solutions, on the other hand, have been subject to only a few AIMD studies, including the characterization of the dissociation of the NaCl in water, 26 the cooperative ionic effects are of the Na + and Cl À on the hydrogen bonding network, 27 and the influence of a static electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…For water molecules around hydrophilic groups, it was found that the retardation effect of hydrophilic amino groups on the hydrogen bond accepting water (HBA water) is comparable with that of hydrophobic groups, but is weaker than the effect on the HBD water. 57,58 Given the discussion above, it is reasonable to classify hydrophobic hydration water and HBA water molecules accepting HBs from NH 2 groups into slow water. The time scales of slow water are indicated by red diamond markers in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For water molecules around hydrophilic groups, it was found that the retardation effect of hydrophilic amino groups on the hydrogen bond accepting water (HBA water) is comparable with that of hydrophobic groups, but is weaker than the effect on the HBD water. 57,58…”
Section: Resultsmentioning
confidence: 99%
“…Wavelet‐based frequency calculations are reliable and fast and can be applied to interfaces, [108] confined water, [109] and aqueous solutions of peptides and polypeptides [110,111] . Further, details of the wavelet method are available in our previous reports [92,104,106,112–114] …”
Section: Computational Detailsmentioning
confidence: 99%
“…Time‐series wavelet method has been used to extract the instantaneous frequency of a specific probe through Fourier transform [99] of the time domain data at each timeframe. Earlier wavelet theorem had been applied to analyze the phenomena of vibrational spectral diffusion in water, [95,100,101] ionic solutions, [102,92] and aqueous solutions of neutral molecules [103–107] . In the previously reported studies, the wavelet was the chosen method for frequency calculations, and it could efficiently reproduce the experimental results with a significant amount of accuracy.…”
Section: Computational Detailsmentioning
confidence: 99%